(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study focuses on the improvement of the CHX-3M2 large dirt cleaning equipment brush to enhance its performance, durability, and efficiency. The CHX- 3M2 brush plays a vital role in various cleaning applications, including industrial, commercial, and residential settings. By optimizing design, materials, and functionality, this research aims to address common challenges associated with cleaning equipment brushes, such as bristle wear, debris removal efficiency, and ergonomic usablity. Through innovative design modifications, material enhancements, and advanced manufacturing techniques, the goal is to develop an improved version of the CHX-3M2 brush that delivers superior cleaning performance and durability while meeting the diverse needs of end-users